FRANCISCAN MEDITATION: THE MIND’S JOURNEY INTO GOD - Ewert H Cousins (Journal of Dharma, 2020)
In comparison with the Orient, the West is far behind in cultivating types and techniques of meditation. Yet there are more meditative riches buried in our cultural past than we Westerners often realize. Awakened by our encounter with Oriental medita- tion-by wandering gurus with a maze of meditation techniques -we Westerners are being spurred to do some archaeological digging into our own past, to embark on a treasure hunt, as it were, in order to retrieve the spiritual wisdom buried in texts .long out of print and in monastic traditions that have been by-passed by the main thrust of Western culture.